Virginia Woolf: Lesbian readings - Barrett, Eileen; Cramer, Patricia (New York University Press, 1997)
The last two decades have seen a resurgence of critical and popular attention to Virginia Woolf's life and work. Such traditional institutions as The New York Review of Books now pair her with William Shakespeare in promotional advertisements; her face is used to sell everything from Barnes & Noble books to Bass Ale. Virginia Woolf: Lesbian Readings represents the first book devoted to Woolf's lesbianism. Divided into two sections, Lesbian Intersections and Lesbian Readings of Woolf's Novels, these essays focus on how Woolf's private and public experience and knowledge of same-sex love influences her shorter fiction and novels. Lesbian Intersections includes personal narratives that trace the experience of reading Woolf through the 60s, 70s, 80s, and 90s. Lesbian Readings of Woolf's Novels provides lesbian interpretations of the individual novels, including Orlando, The Waves, and The Years. Breaking new ground in our understanding of the role Woolf's love for women plays in her major writing, these essays shift the emphasis of lesbian interpretations from Woolf's life to her work.
Keywords: approches et analyses; arts; discipline; europe; lesbianisme; littérature; royaume-uni; régions géographiques; études littéraires

Les lesbiennes dites "masculines", ou quand la masculinité n'est qu'un paysage - Caraglio, Martine (Nouvelles Questions Féministes, 1997)
Le sujet est la construction identitaire des lesbiennes qui se perçoivent elles-mêmes comme masculines et qui sont ainsi perçues par leur entourage: par les lesbiennes aussi bien que par les autres personnes. Le "masculin" est envisagé comme une création dans et par la hiérarchie de genre.L'auteure a mené pendant un an une enquête dans une discothèque; 19 histoires de vie apportent leur témoignage. Au terme de ses recherches, la masculinité en question apparaît: 1) comme une manière supportable d'être une femme pour celles qui ne sereconnaissent pas dans le stéréotype féminin; 2) comme un "paysage", c'est-à-dire comme quelque chose dont la lesbienne trouve les traits dans le système de genres de la société et dont elle s'empare, faute de mieux ou d'autre chose, pour manifester son refus de la position genrée à quoi la société l'assigne.
https://www.jstor.org/stable/40619659
Keywords: 1900-1999; 1990-1999; approches et analyses; genre; lesbianisme; périodes historiques; ressource en ligne

Cross-purposes: Lesbians, feminists, and the limits of alliance - Heller, Dana Alice (Indiana University Press, 1997)
Une collection de quinze essais interdisciplinaires examinant l'histoire, la situation actuelle et l'évolution des alliances lesbiennes avec les féministes américaines. Les contributeurs explorent la signification sociale et esthétique des termes « lesbienne » et « féministe » dans le but de les réformer et de les renforcer.
Keywords: amériques; approches et analyses; discours dominant; hétérosexisme; lesbianisme; personnes lesbiennes; régions géographiques; systèmes d'oppression; états-unis